5-25-77 [videorecording (DVD)] - Johnson, Patrick Read; Daley, John Francis, 1985-; Camp, Colleen, 1953-; Flynn, Neil, 1960-; Pendleton, Austin; Coulter, Steve, 1984-; Chen, Emmi; Jeep, Katie; Streitmatter, Gwen; Mentell, Justin; McLinden, Christopher; Miles, Eric, 1994-; et al. (MVD Visual, 2022)
During the spring of 1977, sci-fi-obsessed teenager Pat Johnson finds himself torn between making 8mm sequels to his favorite movies and pursuing the girl of his dreams, Linda. Desperate to help her son escape his likely future in Wadsworth, Illinois, (population 750), his mother Janet cold-calls the editor of 'American Cinematographer's magazine, and Pat soon finds himself on "the ultimate trip" to Hollywood, becoming the very first outsider to see the film that would change him (and movies) forever...Star Wars. But when Pat returns to his hometown existence, he struggles to choose between chasing a seemingly impossible dream and accepting the comforting familiarity of home.